Biology and Clinical Implications of Fecal Occult Blood Test Screen-Detected Colorectal Cancer. Issue 1 (10th January 2022) - Mendis, Shehara; Hong, Wei; Ananda, Sumitra; Faragher, Ian; Jones, Ian; Croxford, Matthew; Steel, Malcolm; Jalali, Azim; Gard, Grace; To, Yat Hang; Lee, Margaret; Kosmider, Suzanne; et al.
Abstract: Background: Fecal occult blood test (FOBT)–based screening for colorectal cancer (CRC) reduces mortality, with earlier stage at diagnosis a prominent feature. Other characteristics of FOBT screen-detected cancers and any implications for clinical management have not been well explored. Methods: We examined a multisite clinical registry to compare the characteristics and outcomes of FOBT screen-detected CRC via the Australian National Bowel Cancer Screening Program (NBCSP), which is offered biennially to individuals aged 50-74 years, and age-matched non-screen-detected CRC in the same registry. All statistical tests were 2-sided. Odds ratios (ORs) were calculated using the Baptista-Pike method, and hazard ratios via the log-rank method. Results: Of 7153 registry patients diagnosed June 1, 2006, to June 30, 2020, 4142 (57.9%) were aged between 50 and 74 years. Excluding 406 patients with non-NBCSP screen-detected cancers and 35 patients with unknown method of detection, 473 (12.8%) were screen detected via the NBCSP, and 3228 (87.2%) were non-screen detected. Screen-detected patients were younger (mean age = 62.4 vs 64.2 years; P < .001) and more medically fit (OR for ASA score 1-2 = 1.91, 95% confidence interval [CI] = 1.51 to 2.41; P < .001). Pathologic characteristics within each stage favored the screen-detected patients. Stage III screen-detected colon cancers were more likely to receive adjuvant therapy (OR = 3.58, 95% CI = 1.52 to 8.36; P = .002). Screen-detected patients had superior relapse-free (hazard ratio = 0.41, 95% CI = 0.29 to 0.60; P < .001) and overall survival (hazard ratio = 0.22, 95% CI = 0.15 to 0.35; P < .001), which was maintained in matched stage comparisons and multivariable analysis. Conclusions: Beyond stage at diagnosis, multiple other factors associated with a favorable outcome are observed in FOBT screen-detected CRC. Given the substantial stage-by-stage differences in survival outcomes, if independently confirmed, individualized adjuvant therapy and surveillance strategies could be warranted for FOBT screen-detected cancers.